The Influence of Elderly Posyandu Management on Health and Quality of Life at the Sinoa Community Health Center in Bantaeng - Samsualam; Andi Tenri Agung; Muh. Multazam; Haeruddin; Nurlinda, Andi; Yuliaty; Amir, Haeril (Universitas STRADA Indonesia, 2023)
Background: The Elderly Posyandu (integrated healthcare center) at the Sinoa Community Health Center in Bantaeng has an important role in maintaining the quality of life of the elderly in the community. Apart from providing health services, this smallest service unit will also facilitate various non-medical activities so that the elderly have a place to work and be active. Purpose: This is the researchers' idea to examine whether there is an influence of the Elderly Posyandu program on the quality of life of the elderly in the Sinoa sub-district, Bantaeng. Methods: This study used a quantitative method with a cross-sectional design. The population of this study was 210 elderly with a total sample of 136 elderly selected by means of proportional stratified random sampling. Data collection was carried out by means of interviews using a questionnaire. The collected data were analyzed using the path analysis test. Results: Results of path analysis, where the independent variable (predictor) is the Elderly Posyandu variable include extension (X1) and elderly gymnastics (X2), the mediation variable is the elderly health (Y), and the dependent variable (response) is the quality of life of the elderly (Z), show that periodic medical check-up (X3) through the elderly health variable (Y) has the greatest indirect influence on the quality of life of the elderly in the Sinoa sub-district, Bantaeng. Conclusion: Posyandu management for the elderly is very important because it will affect the quality of life of the elderly. The management in question includes the elderly Posyandu program.